Canadian International Petroleum Conference 2005
DOI: 10.2118/2005-194
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Solvent and Well Geometry for Production of Heavy Oil by Cyclic Solvent Injection

Abstract: The Vapor Extraction (VAPEX) process has been proposed as a viable alternative to steam-based heavy oil recovery methods. In this process, a vaporized solvent is injected into a horizontal well placed higher in the formation, and the diluted heavy oil is produced by gravity drainage from a horizontal production well situated below. One shortcoming of this process is the slow diffusion of the solvent into the bulk of the oil.The mass transfer mechanism in the VAPEX process involves molecular diffusion and conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Previous experimental studies have shown that heavy oil recovery during the CSI process is affected by different variables such as diffusion and convection (Ahadi and Torabi, 2018), gravity drainage (Ivory et al, 2010), pressure depletion rate (Du, et al, 2014), foamy oil flow (Bjorndalen, et al, 2012), the presence of wormholes (Du et al, 2015), type of solvent (Qazvini Firouz and Torabi, 2014;Qi, 2005) and solvent injection sequence (Jamaloei et al, 2012;2013). However, experimental results associated with heavy oil recovery obtained by different authors vary when compared to each other and to field applications.…”
Section: Summary and Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous experimental studies have shown that heavy oil recovery during the CSI process is affected by different variables such as diffusion and convection (Ahadi and Torabi, 2018), gravity drainage (Ivory et al, 2010), pressure depletion rate (Du, et al, 2014), foamy oil flow (Bjorndalen, et al, 2012), the presence of wormholes (Du et al, 2015), type of solvent (Qazvini Firouz and Torabi, 2014;Qi, 2005) and solvent injection sequence (Jamaloei et al, 2012;2013). However, experimental results associated with heavy oil recovery obtained by different authors vary when compared to each other and to field applications.…”
Section: Summary and Future Workmentioning
confidence: 99%
“…Previous experimental studies (Jia, 2014;Qi, 2005;Ivory et al, 2010) have pointed out propane as the most efficient solvent for enhanced heavy oil recovery. From experiments conducted in core # 1 (see Chapter 4), it was found that gravity forces played an important role on the oil recovery when a solvent mixture of 70% CH4 -30% C3H8 was cyclic injected.…”
Section: Introductionmentioning
confidence: 99%
“…Previous experimental studies have shown that heavy oil recovery during the CSI process is affected by different variables such as diffusion and convection (Ahadi and Torabi, 2018), gravity drainage (Ivory et al, 2010), pressure depletion rate (Du, et al, 2014), foamy oil flow (Bjorndalen, et al, 2012), the presence of wormholes , type of solvent (Qazvini Firouz and Torabi, 2014;Qi, 2005) and solvent injection sequence (Jamaloei et al, 2012;2013). However, experimental results associated with heavy oil recovery obtained by different authors vary when compared to each other and to field applications.…”
Section: Summary and Future Workmentioning
confidence: 99%